Analisis Antusias Mahasiswa dalam Belajar Ekonomi Kreatif dalam Mengembangkan UMKM: Usaha Mikro Kecil Menengah - Ginting, Della Aulia Br.; Samosir, Jelita Maria Christine; Nabillah, Rana; Lubis, Putri Kemala Dewi (Masyarakat Ekonomi Syariah Bogor, 2024)
Students' enthusiasm for developing MSMEs is influenced by studying the creative economy. Therefore, it is important to study creative economics because it opens students' insight into the potential of creative economics and innovation. This research uses a qualitative paradigm. The research was conducted to find out what enthusiasm students have in learning creative economics in developing MSMEs (Micro Small and Medium Enterprises). We took this research through interviews using three questions to students who were or were already running MSMEs. From the questions included, more students are interested in creating MSMEs after studying the creative economy and student creativity and innovation can develop further after studying the creative economy.